Maternal antibiotic exposure-mediated alterations in basal, and allergen-induced lung function are associated with altered recruitment of eosinophils to the developing lung - Wilburn, Adrienne N; Korkmaz, Rabia Ülkü; McAlees, Jaclyn W; Hargis, Julie M; Shirdel, Schmaiel; Lingel, Imke; Watanabe-Chailland, Miki; Romick-Rosendale, Lindsey; Schmudde, Inken; Bridges, James P; Chougnet, Claire A; Deshmukh, Hitesh; et al. (Frontiers in Immunology, 2025)
IntroductionEarly-life dysbiosis is associated with increased risk of asthma development but the underlying mechanisms remain unclear. Although eosinophils have been reported in the developing lung, their contributions to alveolar morphogenesis and lung mechanics have not been functionally interrogated.MethodsMaternal exposure to antibiotics (ABX) was used to induce early-life offspring dysbiosis, and the effects on lung function and development was assessed. Similar measurements were made in mice lacking eosinophils due to genetic modification, or administration of IL-5 blocking agents.ResultsABX exposure between Embryonic Day 15 (E15) and post-natal day 28 (PN28), increased allergen-induced, and baseline airway hyperreactivity (AHR). Similar observations were made when maternal ABX exposure was limited to PN10 to PN20. Complete characterization of baseline lung mechanics demonstrated downward-shifted pulmonary PV loops, increased small airway resistance, decreased compliance, and reduced inspiratory capacity at weaning and 14 months of age. Consistent with observation of small airway dysfunction, offspring of ABX-exposed dams demonstrated significantly smaller alveoli at multiple stages of lung development. Examination of recruitment to developing lungs demonstrated an exaggerated recruitment of eosinophils at key developmental periods (PN14) in offspring of ABX-exposed dams. Mice with fewer eosinophils (through genetic knockout, or treatment with anti-IL-5) display altered patterns of lung mechanics opposite to that seen in offspring of ABX-exposed dams.DiscussionThese data underscore an underappreciated role of eosinophils in homeostatic lung development and suggest that early life modulation of pulmonary eosinophil activity has long-term effects on susceptibility to the development of chronic lung diseases such as asthma.